Are You Being Asked? Impacts of Respondent Selection on Measuring Employment - Kilic, Talip; Van den Broeck, Goedele; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2020)
Accurate estimates of men's and women's employment are at the heart of understanding sources of productivity and economic growth and designing well-targeted, gender-sensitive labor policies. How respondent selection in household and labor force surveys affects these estimates is a key question, for which experimental evidence outside high-income settings is limited. Leveraging two concurrent, national surveys in Malawi that differed in their approach to respondent selection, the analysis shows that, compared with the best practice of privately interviewing adults about their employment outcomes, the common "business-as-usual" approach that permits the use of proxy respondents and non-private/group interviews leads to significant underreporting of employment across a range of wage and self-employment activities, with stronger effects for women and for a longer (12-month) recall period. Under the business-as-usual approach, the main factors linked to underreporting include household wealth, proxy reporting, and potential difficulties associated with interpreting/answering questions on household non-farm enterprises.